'All the Rest is Dance': another look at Levinas. Issue 1 (2nd January 2016) - Bazzano, Manu
Abstract: This paper begins by tracing the growing influence of Levinas's thought in the humanities. Psychotherapy in particular has drawn on Levinas's original contribution to ethics and is often inscribed within an existing dialogical frame of symmetry. The article discusses facets of Levinasian thought which have been neglected in psychotherapy, namely the notion of separation, in turn linked to the notions of asymmetry and of the traumatic subject, all at variance with dialogical therapy. A second, equally overlooked aspect of Levinas's philosophy examined here concerns his politics. Some of the implications highlighted here are controversial: these relate to Levinas 'naive Zionism' and a prejudiced position in relation to Arab culture. Others are enlightening even if undeveloped: these relate to Levinas's decolonial thinking of the 1970s. The paper reflects tangentially on the author's clinical work, and calls for a more nuanced appreciation of Levinas's philosophy which does not shy away from critique.